Hydraulic Fracture Propagation under Varying In-situ Stress Conditions of Reservoirs. (2017) - Wasantha, P.L.P.; Konietzky, H.
Abstract: In-situ stress state in deep reservoirs is highly variable due to many factors and it markedly influence the propagation behavior of hydraulic fractures. The direction and extent of hydraulic fracture propagation are predominantly controlled by the in-situ stress state of reservoirs. We conducted distinct element method-based numerical simulations to explore the behavior of hydraulic fracture propagation and containment under varying in-situ stress conditions and fluid injection rates. The results revealed that even a small contrast of minor principal stress between pay-zone and adjacent bounding zones can cause a significant hydraulic fracture containment. Simulations performed under different injection rates showed that the hydraulic fracture containment is also influenced by the injection rate and higher injection rates tend to increase the hydraulic fracture penetration into the adjacent bounding zones. Overall, the results of the present study generally suggest that the fracture propagation during hydraulic fracturing is not an unconstrained event as one would imagine and natural barriers such as varying in-situ stresses, which are common in deep reservoirs, often limit fracture propagation to a certain finite extent. In addition, operational conditions such as fluid injection rate can be selected appropriately to control the hydraulic fracture propagation into unproductive bounding strata.